Robot-assisted versus fluoroscopy-assisted kyphoplasty in treatment of severe osteoporotic vertebral compression fractures in the old patients: a retrospective study - Peng Liu; Jiang Hu; Wei Zhang; Fei Wang; Liuyi Tang; Weijun Zhou; Shu Lin (BMC Musculoskeletal Disorders)
Abstract Background Although percutaneous kyphoplasty (PKP) is used to treat severe osteoporotic vertebral compression fractures (OVCF), the unsatisfactory effect of bone cement reduction and leakage is a concern. In recent years, the application of surgical robots in the field of orthopaedics has shown promising prospects. Since 2017, our hospital has used surgical robot-assisted PKP to treat severe OVCF. Methods One hundred and fifty-five old patients with severe OVCF who had undergone PKP were retrospectively analyzed and stratified into two groups: robot-assisted (n = 88) and fluoroscopy-assisted (n = 67). The surgical time, intraoperative radiation dose, surgical efficacy (analgesic effect and limb function), imaging evaluation (accuracy of puncture, distribution of bone cement, reduction of vertebral height, and rectification of Cobb angle), and leakage of bone cement were analyzed to evaluate the potential advantages of robot-assisted PKP in the treatment of severe OVCF. Results There were significant differences in surgical time (P < 0.001), intraoperative radiation dose (P < 0.001), analgesic effect (P = 0.001), accuracy of puncture (P = 0.008), distribution (P = 0.013), and leakage of bone cement (P = 0.019) between the two groups. However, postoperative limb function (P = 0.612), reduction in vertebral height (P = 0.068), and rectification of the Cobb angle (P = 0.243) were similar in both groups. Conclusions The application of robot-assisted PKP for treating severe OVCF (Genant Grade III) can slightly shorten surgery time and significantly reduce intraoperative total radiation exposure for both patients and clinicians. Additionally, it improves puncture accuracy and reduces the cement leakage rate, ultimately achieving satisfactory pain relief. However, in terms of functional recovery, no significant differences were observed between the two approaches.